第55次日本南極地域観測隊気象部門報告2014 - 山本, 浩嗣; ヤマモト, ヒロツグ; 今泉, 貴嗣; イマイズミ, タカシ; 朝原, 信長; アサハラ, ノブナガ; 大竹, 潤; オオタケ, ジュン; 佐伯, 悠樹; サエキ, ユウキ; Yamamoto, Hirotsugu; Imaizumi, Takashi; et al. (国立極地研究所, 2020)
この報告は第55 次日本南極地域観測隊気象部門が，2014 年2 月1 日～2015 年1 月31 日まで昭和基地において行った気象観測結果をまとめたものである．観測方法，測器，統計方法等は第54 次隊と同様である．越冬期間中の特徴のある気象状況は次のものがあげられる． 1）越冬期間中のブリザードの発生回数は23 回と1981～2010 年のブリザードの平均回数24.6 を下回ったが，11 月を除いて毎月ブリザードが発生した．2015年1 月のブリザードでは，第55 次隊の記録では最大となる日最大風速41.8 m/s，日最大瞬間風速51.4 m/s を記録し，1 月の日最大風速及び日最大瞬間風速の一位を更新した． 2）2014 年2 月の月間日照時間114.6 時間は，2 月の月間日照時間の少ない方からの一位を更新した． 3）2014 年3 月18 日に，統計を開始した1981 年2 月以降で2002 年7 月11 日と並び，相対湿度の最小値（18%）を記録した． 4）昭和基地上空のオゾン全量は，8 月中旬から11 月中旬までオゾンホールの目安となる220 m atm-cm を度々下回り，10 月7 日に2014 年の最小値である139 m atm-cm を記録した． This report describes the results of meteorological observations at Syowa Station from February 1st, 2014 to January 31st, 2015, carried out by the Meteorological Observation Team of the 55th Japanese Antarctic Research Expedition (JARE-55). The observation methods, instruments, and statistical methods used by JARE-55 were the same as those used by the JARE-54. Remarkable weather phenomena observed during the period of JARE-55 are as follows: 1) The number of occurrences of the blizzard was 23 times, which was smaller than 24.6 of annually average times from 1981 to 2010. Blizzard occurred in January 2015, the maximum wind speed (10-minute average) was 41.8 m/s, the maximum instantaneous wind speed was 51.4 m/s, both records for this month and during the period of JARE-55. Blizzard occurred every month except November. 2) The monthly sunshine duration in February 2014 was only 114.6 hours, a record low for this month. 3) On March 18th, 2014, the daily low relative humidity was 18%, which was the same value on July 11th, a record low since February 1981. 4) The amount of total ozone over Syowa Station from mid-August to mid-November was often less than 220 m atm-cm used as a target for the ozone hole for most of this period. The value for October 7th was 139 m atm-cm, which marked the minimum value of year 2014. departmental bulletin paper